Silver plating material and manufacturing method thereof
By forming a silver surface layer containing carbon and sulfur on the silver plating material, the problem of insufficient peeling and wear resistance in high temperature and high humidity environments is solved, and the tightness and resistance of the existing silver plating materials are achieved under high temperature and high humidity. Improved wearability.
Patent Information
- Application Number
- CN202280094458.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-28
- Filing Date
- 2022-12-23
- Publication Date
- 2025-01-10
AI Technical Summary
The existing silver-plating materials are prone to peeling the substrate coating film in high temperature and high humidity environments, and are not able to meet the clinging and wear resistance of the contacts or terminal components of the connector or switch.
The surface layer composed of silver containing carbon and sulfur is formed by electroplating on the raw material. It is preferred to use a potassium silver cyanide or an aqueous solution of potassium cyanide, sodium cyanide and benzothiazoles to control the electroplating conditions to form a plating containing carbon and sulfur. Silver film ensures the thickness of the base silver-plated film and the microcrystal particle size of the surface layer, and improves the clinging and wear resistance of the silver-plated material.
It is achieved that the silver-plated film is not easy to peel off in high temperature and high humidity environments, improves the clinging and wear resistance of silver-plated materials, and meets the needs of contacts or terminal components of connectors or switches.
Smart Images

Figure CN119301312A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a silver-plated material and a method for producing the same, and in particular to a silver-plated material used as a material for contact or terminal parts of connectors, switches, relays, etc. used in vehicle-mounted or household electrical wiring and a method for producing the same. Background Art
[0002] Conventionally, materials such as contacts and terminal parts of connectors and switches have been plated with tin, silver or gold plating based on the required properties such as electrical properties and weldability, using relatively inexpensive raw materials such as copper, copper alloys and stainless steel that have excellent corrosion resistance and mechanical properties.
[0003] Tin-plated materials, which are materials such as copper, copper alloys, and stainless steel, are inexpensive, but have poor corrosion resistance in high-temperature environments. Gold-plated materials, which are materials such as these, are gold-plated, and have excellent corrosion resistance and high reliability, but are more expensive. On the other hand, silver-plated materials, which are materials such as these, are inexpensive compared to gold-plated materials and have excellent corrosion resistance compared to tin-plated materials.
[0004] Furthermore, materials of contacts and terminal parts of connectors, switches, and the like are also required to have wear resistance associated with insertion and removal of the connector and sliding of the switch.
[0005] However, silver-plated materials are soft and easily abraded. Therefore, when used as materials for connection terminals, etc., there are problems such as sticking due to insertion and removal or sliding, which easily causes viscous wear, and the surface is scraped when the connection terminal is inserted, which increases the friction coefficient and the insertion force.
[0006] In order to solve such a problem, a method of increasing the hardness of the silver-plated material by adding an element such as antimony to the silver plating is known (for example, see Patent Document 1).
[0007] However, if an element such as antimony is contained in silver plating as in the method of Patent Document 1, although silver is alloyed to improve hardness, improvement in wear resistance is insufficient, and a silver-plated material having excellent wear resistance is desired.
[0008] In order to solve such a problem, a method for producing a silver-plated material having better wear resistance than before is proposed: in the method for producing a silver-plated material by electroplating in a silver-plating solution composed of an aqueous solution containing potassium silver cyanide or silver cyanide, potassium cyanide or sodium cyanide, and benzothiazoles or derivatives thereof to form a surface layer composed of silver on a raw material, the concentration of free cyanide in the silver-plating solution is set to A (g / L), the concentration of the benzothiazole component of benzothiazoles or derivatives thereof in the silver-plating solution is set to B (g / L), the temperature of the silver-plating solution is set to C (°C), and the current density of the electroplating is set to D (A / dm 2 ), by electroplating to make (BC / A)2 / D at 10(℃ 2 ·dm 2 / A) or above (see, for example, Patent Document 2). Prior art literature Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2009-79250 (Paragraphs 0003 to 0004) Patent Document 2: Japanese Patent No. 6916971 (Paragraph 0013) Summary of the invention Technical problem to be solved by the invention
[0010] However, the silver-plated material produced by the method of Patent Document 2 has a problem that the silver-plated film is easily peeled off from the base plated film in a high-temperature and high-humidity environment when the silver-plated film is formed on the raw material via the base plated film.
[0011] Therefore, for the silver-plated material with excellent wear resistance manufactured by the method of Patent Document 2, it is desired to provide a silver-plated material with excellent adhesion, in which the silver-plated film is not easily peeled off from the base plated film under a high temperature and high humidity environment when the silver-plated film is formed on the raw material via the base plated film.
[0012] Therefore, in view of such conventional problems, the present invention aims to provide a silver-plated material and a method for producing the same, in which when a silver-plated film is formed on a raw material via a base plated film, the silver-plated film is not easily peeled off from the base plated film under a high temperature and high humidity environment and has excellent adhesion. Solutions to technical problems
[0013] The present inventors have conducted intensive studies to solve the above-mentioned technical problems, and as a result, have found that, if a base silver-plated film is formed on a raw material via a base plated film, and then a surface layer composed of silver containing carbon and sulfur (a silver-plated film containing carbon and sulfur) is formed on the base silver-plated film by electroplating in a silver plating solution composed of an aqueous solution containing potassium silver cyanide or silver cyanide, potassium cyanide or sodium cyanide, and benzothiazoles or derivatives thereof, a silver-plated material can be produced in which the silver-plated film is not easily peeled off from the base plated film under a high temperature and high humidity environment when the silver-plated film is formed on the raw material via the base plated film, and the silver-plated material has excellent adhesion, thereby completing the present invention.
[0014] That is, the method for producing a silver-plated material of the present invention is characterized in that, after forming a base silver-plated film on a raw material via a base plated film, electroplating is performed in a silver plating solution composed of an aqueous solution containing potassium silver cyanide or silver cyanide, potassium cyanide or sodium cyanide, and benzothiazoles or derivatives thereof, thereby forming a surface layer composed of silver containing carbon and sulfur on the base silver-plated film.
[0015] In the method for manufacturing the silver-plated material, the thickness of the base silver-plated film is preferably 0.06 to 15 μm. In addition, the benzothiazole is preferably mercaptobenzothiazole, and the derivative of the benzothiazole is preferably an alkali metal salt of the benzothiazole, and the alkali metal salt is preferably a sodium salt. In addition, the base plated film is preferably composed of copper, nickel or an alloy thereof, and the raw material is preferably composed of copper or a copper alloy.
[0016] In addition, the silver-plated material of the present invention is characterized in that a base silver-plated film is formed on the raw material via a base plated film, a surface layer composed of silver containing carbon and sulfur is formed on the base silver-plated film, the Ag atomic concentration in the base silver-plated film is higher than 95at%, the S atomic concentration is lower than 0.6at%, and the ratio of the C atomic concentration to the Ag atomic concentration is lower than 3%, and the Ag atomic concentration in the surface layer composed of silver containing carbon and sulfur is less than 95at%, the S atomic concentration is more than 0.6at%, and the ratio of the C atomic concentration to the Ag atomic concentration is more than 3%. In the silver-plated material, the thickness of the base silver-plated film is preferably 0.06 to 15μm. In addition, the average microcrystalline grain size of silver in the silver-plated material is preferably less than 100nm, and the Vickers hardness HV of the surface of the silver-plated material is preferably 70 to 160. Furthermore, the base plated film is preferably composed of copper, nickel or their alloys, and the raw material is preferably composed of copper or a copper alloy. In addition, it is preferred that the total concentration of S atoms derived from the mercapto group of mercaptobenzothiazole and the S element of the five-membered ring in the surface layer composed of silver containing carbon and sulfur is 0.3 at% or more, and the total concentration of S atoms derived from the mercapto group of mercaptobenzothiazole and the S element of the five-membered ring in the base silver-plated film is less than 0.3 at%. In addition, for the surface layer composed of silver containing carbon and sulfur, the total concentration of S atoms determined from the spectrum having a peak in the range of 161.6 to 162.9 eV and the total concentration of S atoms determined from the spectrum having a peak in the range of 163.2 to 164.5 eV when measured by X-ray photoelectron spectroscopy is 0.3 at% or more; and for the base silver-plated film, the total concentration of S atoms determined from the spectrum having a peak in the range of 161.6 to 162.9 eV and the total concentration of atoms determined from the spectrum having a peak in the range of 163.2 to 164.5 eV when measured by X-ray photoelectron spectroscopy is preferably less than 0.3 at%. Effects of the Invention
[0017] According to the present invention, a silver-plated material having excellent adhesion and a method for producing the same can be provided, in which the silver-plated film is not easily peeled off from the base plated film under a high temperature and high humidity environment when a silver-plated film is formed on a raw material via a base plated film. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a scanning electron microscope photograph (SEM image) of the cross section of the silver-plated material of Example 10 at 50,000 times magnification. Figure 2This is a SEM image of the cross section of the silver-plated material of Comparative Example 1 at 50,000 times magnification. DETAILED DESCRIPTION
[0019] In an embodiment of the method for producing a silver-plated material of the present invention, a strike silver-plated film is formed on a raw material (preferably made of copper or a copper alloy) via a base plated film (preferably made of copper, nickel or an alloy thereof) (preferably having a thickness of 0.01 to 10 μm, more preferably having a thickness of 0.5 to 2 μm), and after a base silver-plated film (preferably having a thickness of 0.06 to 15 μm, more preferably 0.10 to 10 μm, and most preferably 0.15 to 5 μm including the strike silver-plated film) is formed on the strike silver-plated film, electroplating is performed in a silver plating solution composed of an aqueous solution containing potassium silver cyanide or silver cyanide, potassium cyanide or sodium cyanide, and benzothiazoles or derivatives thereof, thereby forming a surface layer composed of silver containing carbon and sulfur (preferably having a thickness of 0.1 to 5.0 μm, more preferably 0.5 to 3.0 μm, and most preferably 0.5 to 2.0 μm) on the base silver-plated film.
[0020] The base silver-plated film can be formed by plating in a silver plating solution composed of an aqueous solution containing potassium silver cyanide (KAg(CN)2), potassium cyanide (KCN) and selenium at a current density of 1 to 10 A / dm 2 The electroplating is performed for 1 to 90 seconds.
[0021] Among them, benzothiazole (C7H5NS) is preferably a heterocyclic compound with a benzene skeleton and a thiazole skeleton, and benzothiazoles are preferably benzothiazoles with a sulfhydryl group (-SH) such as 2-mercaptobenzothiazole. In addition, as derivatives of benzothiazoles, sodium 2-mercaptobenzothiazole (sodium mercaptobenzothiazole (SMBT)), zinc-2-mercaptobenzothiazole, 5-chloro-2-mercaptobenzothiazole, 6-amino-2-mercaptobenzothiazole, 6-nitro-2-mercaptobenzothiazole, 2-mercapto-5-methoxybenzothiazole, etc. can be used. Among the derivatives of these benzothiazoles, alkali metal salts of benzothiazoles are preferred, and sodium salts of benzothiazoles such as sodium 2-mercaptobenzothiazole (sodium mercaptobenzothiazole (SMBT)) are preferred.
[0022] If benzothiazoles (such as mercaptobenzothiazole) or their alkali metal salts (preferably sodium salts) are added as organic additives to the (cyanide) silver plating solution for electroplating (silver plating), the organic additive (at least a part of it) is incorporated into the surface layer composed of silver, and it is believed that the friction coefficient of the surface layer can be reduced by the lubricating effect of the organic additive. Moreover, the use of mercaptobenzothiazole as a benzothiazole can improve the production efficiency of the silver-plated material. In addition, since the organic additive is incorporated into the surface layer composed of silver, when the silver-plated material is used as a material such as a connection terminal, the sticking caused by plugging or sliding can be suppressed, so that the wear resistance is improved. In particular, electroplating under the above conditions can produce a silver-plated material with better wear resistance than before.
[0023] In the method for producing the silver-plated material, the concentration of free cyanide in the silver-plating solution is preferably 3 to 70 g / L (more preferably 10 to 70 g / L, most preferably 15 to 60 g / L), the concentration of the benzothiazole component in the silver-plating solution is preferably 2 to 100 g / L (more preferably 5 to 90 g / L, more preferably 8 to 80 g / L, most preferably 10 to 70 g / L), and the concentration of silver in the silver-plating solution is preferably 15 to 140 g / L (more preferably 15 to 125 g / L, most preferably 20 to 110 g / L). In addition, the concentration of potassium silver cyanide or silver cyanide in the silver plating solution is preferably 30 to 260 g / L (more preferably 30 to 25 g / L, most preferably 35 to 220 g / L), the concentration of potassium cyanide or sodium cyanide in the silver plating solution is preferably 10 to 200 g / L (more preferably 20 to 185 g / L, further preferably 30 to 160 g / L, most preferably 40 to 115 g / L), and the concentration of benzothiazole or its alkali metal salt in the silver plating solution is preferably 3 to 100 g / L (more preferably 10 to 90 g / L, most preferably 15 to 80 g / L). In addition, the electroplating (silver plating) is preferably carried out at a liquid temperature of 15 to 50°C, more preferably at a liquid temperature of 18 to 47°C. In addition, the electroplating (silver plating) is preferably carried out at a current density of 0.5 to 12 A / dm 2 It is carried out at a temperature of 1.5 to 10 A / dm 2 In addition, in order to form a good silver-plated film, it is preferred that the current density is higher, at 2A / dm 2 More preferably, 3A / dm 2 above.
[0024] In an embodiment of the silver-plated material of the present invention, a strike silver-plated film is formed on a raw material (preferably made of copper or a copper alloy) via a base plated film (preferably made of copper, nickel or an alloy thereof) (preferably with a thickness of 0.01 to 10 μm, more preferably with a thickness of 0.5 to 2 μm), a base silver-plated film (preferably with a thickness of 0.06 to 15 μm, more preferably with a thickness of 0.10 to 10 μm, and most preferably with a thickness of 0.15 to 5 μm including the strike silver-plated film) is formed on the strike silver-plated film, and a base silver-plated film (preferably with a thickness of 0.1 to 5.0 μm, more preferably with a thickness of 0.5 to 3.0 μm, and most preferably with a thickness of 0.15 to 5 μm) is formed on the base silver-plated film. The surface layer (preferably 0.5 to 2.0 μm) composed of silver containing carbon and sulfur, the Ag atomic concentration in the base silver-plated film is higher than 95 at% (preferably above 97 at%), the S atomic concentration is lower than 0.6 at% (preferably below 0.5 at%), and the ratio of the C atomic concentration to the Ag atomic concentration is lower than 3% (preferably below 2%), the Ag atomic concentration in the surface layer composed of silver containing carbon and sulfur is lower than 95 at% (preferably above 80 at% and below 93 at%), the S atomic concentration is higher than 0.6 at% (preferably above 0.7 at% and below 5 at%), and the ratio of the C atomic concentration to the Ag atomic concentration is higher than 3% (preferably above 5% and below 20%). In addition, the average microcrystalline grain size of the silver in the silver-plated material is preferably below 100 nm, and the Vickers hardness HV of the surface of the silver-plated material is preferably 70 to 160. In addition, the total concentration of S atoms of the mercapto group and the five-membered ring S element of sodium mercaptobenzothiazole in the surface layer composed of silver containing carbon and sulfur is preferably greater than 0.3at%, more preferably greater than 0.4at%, and the total concentration of S atoms of the mercapto group and the five-membered ring S element of sodium mercaptobenzothiazole in the base silver-plated film is preferably less than 0.3at%, more preferably less than 0.2at%. In addition, for the surface layer composed of silver containing carbon and sulfur, when measured by X-ray photoelectron spectroscopy, the total of the S atomic concentration obtained from the spectrum with a peak in the range of 161.6 to 162.9 eV and the S atomic concentration obtained from the spectrum with a peak in the range of 163.2 to 164.5 eV is preferably greater than 0.3 at%, and more preferably greater than 0.4 at%; for the base silver-plated film, when measured by X-ray photoelectron spectroscopy, the total of the S atomic concentration obtained from the spectrum with a peak in the range of 161.6 to 162.9 eV and the S atomic concentration obtained from the spectrum with a peak in the range of 163.2 eV to 164.5 eV is preferably less than 0.3 at%, and more preferably less than 0.2 at%. Example
[0025] Hereinafter, embodiments of the silver-plated material and the method for producing the same according to the present invention will be described in detail.
[0026] [Example 1] First, as a substrate (material to be plated), a rolled plate composed of oxygen-free copper (C10201 / 2H) of 67mm×50mm×0.3mm is prepared. As a pretreatment of the material to be plated, the material to be plated and the SUS plate are placed in an alkaline degreasing solution, with the material to be plated as the cathode and the SUS plate as the anode, and electrolytic degreasing is carried out for 30 seconds at a voltage of 5V. After washing with water, pickling is carried out in 3% sulfuric acid for 15 seconds, and then washing with water.
[0027] Next, in a matte nickel plating solution consisting of an aqueous solution containing 540 g / L nickel sulfamate tetrahydrate, 25 g / L nickel chloride, and 35 g / L boric acid, the pretreated material to be plated was used as the cathode and the nickel electrode plate was used as the anode. The solution was stirred at 500 rpm with a stirrer and a current density of 7 A / dm was applied at a liquid temperature of 50°C. 2 Electroplating (matte nickel plating) was performed for 70 seconds to form a matte nickel plating film as a base plating film. The thickness of the central portion of the base plating film was measured with a fluorescent X-ray film thickness meter (SFT-110A manufactured by Hitachi High-Technologies Corporation) and found to be 1 μm.
[0028] Then, in an impact silver plating solution consisting of an aqueous solution containing 3 g / L potassium silver cyanide (KAg(CN)2) and 90 g / L potassium cyanide (KCN), the plated material having a base plating film formed thereon was used as a cathode and a titanium electrode plate coated with platinum was used as an anode. The mixture was stirred at 500 rpm with a stirrer while a current density of 2.0 A / dm was applied at room temperature (25°C). 2 The electroplating was performed for 10 seconds to form an impact silver plating film with a thickness of about 0.01 μm, and then the impact silver plating solution was fully rinsed off by water.
[0029] Subsequently, in a silver plating solution (selenium concentration 37 mg / L) consisting of an aqueous solution containing 175 g / L potassium silver cyanide (KAg(CN)2), 95 g / L potassium cyanide (KCN) and potassium selenocyanate, the plated material formed with the impact silver plating film was used as the cathode and the silver electrode plate was used as the anode. The solution was stirred at 500 rpm with a stirrer and the current density was 2.3 A / dm at a liquid temperature of 18°C. 2 Electroplating (silver plating) was performed for 3 seconds to form a base silver plating film. The thickness of the central portion of the base silver plating film (the thickness of the central portion of the base silver plating film including the impact silver plating film) was measured with the fluorescent X-ray film thickness meter and found to be 0.06 μm.
[0030] Then, in a silver plating solution (silver concentration 95 g / L, free cyanide concentration 38 g / L, benzothiazole component (BT) concentration 21 g / L) composed of an aqueous solution containing 175 g / L potassium silver cyanide (KAg(CN)2), 95 g / L potassium cyanide (KCN), and 30 g / L of sodium 2-mercaptobenzothiazole (sodium mercaptobenzothiazole (SMBT)), the plated material having a base silver plating film formed thereon was used as a cathode and the silver electrode was used as an anode. The mixture was stirred at 500 rpm with a stirrer and a current density of 7 A / dm was applied at a liquid temperature of 35°C. 2 Electroplating (silver plating) was performed for 18 seconds to form a silver-plated film. The thickness of the central part of the silver-plated film was measured with the above-mentioned fluorescent X-ray film thickness meter, and the result was 1.06μm. In addition, the free cyanide concentration and the concentration of the benzothiazole component were calculated by free cyanide concentration = KCN concentration × (molecular weight of CN 26.02 / molecular weight of KCN 65.12) and the concentration of the benzothiazole component = SMBT concentration × (molecular weight of benzothiazole (C7H5NS) 135.19 / molecular weight of SMBT 189.23).
[0031] The Vickers hardness HV of the surface (three locations on the surface) of the silver-plated material thus obtained was measured in accordance with JIS Z2244 using a microhardness tester (HM-221 manufactured by Mitutoyo Corporation) with a measuring load of 10 gf applied for 10 seconds. The result was an average of 139.2.
[0032] In addition, the wear resistance was evaluated by the following wear test: two pieces of the above-mentioned silver-plated material were prepared, one piece was indented (R = 1.5 mm on the inside) and used as an indenter, and the other piece was used as a flat evaluation sample. The indenter was pressed on the evaluation sample with a fixed load (5N) using a precision sliding tester (CRS-G2050-DWA manufactured by Yamazaki Seiki Laboratories, Ltd.) while continuously performing a reciprocating sliding motion (sliding distance 5 mm, sliding speed 1.67 mm / s) until the material was exposed, and the center of the sliding mark of the silver-plated material was observed at a magnification of 100 times using a microscope (VHX-1000 manufactured by Keyence Corporation) to confirm the wear state of the silver-plated material. As a result, it was confirmed that the material was not exposed even after 400 reciprocating sliding motions, and the wear resistance was excellent.
[0033] In addition, two sheets of the above-mentioned silver-plated material were prepared, one sheet was indented (inner side R = 1.5 mm) and used as an indenter, and the other sheet was used as a flat evaluation sample. A precision sliding tester (CRS-G2050-DWA manufactured by Yamazaki Seiki Laboratories, Ltd.) was used to press the indenter against the evaluation sample with a fixed load (5 N) while continuously performing a sliding action (sliding distance 5 mm, sliding speed 1.67 mm / s). The force applied in the horizontal direction during the sliding action was measured and its maximum value F was found. The dynamic friction coefficient (μ) between the flat test piece and the indented test piece was calculated from μ = F / N, and the maximum value of the dynamic friction coefficient was 0.39.
[0034] In addition, the crystallite size in the direction perpendicular to the crystal plane of each of the (111) plane, (200) plane, (220) plane and (311) plane on the surface of the silver-plated material was calculated using the Scherrer formula based on the half-width of each peak of the crystal plane peak ((111) peak appearing near 38°, (200) peak appearing near 44°, (220) peak appearing near 64° and (311) peak appearing near 77°) of the X-ray diffraction spectrum (XRD spectrum) obtained by an XRD analysis device (Smart Lab, a fully automatic multifunctional horizontal X-ray diffractometer manufactured by Rigaku Corporation), and the weighting based on the orientation ratio of each crystal plane was performed to calculate the average crystallite size from the weighted average of the crystallite sizes of each crystal plane. As a result, the average crystallite size of silver in the silver-plated material was 161.6 angstroms (16.16 nm). In addition, as the above-mentioned orientation ratio, the value obtained as follows (corrected intensity) is used: using an X-ray diffraction (XRD) analysis device (Smart Lab, a fully automatic multifunctional horizontal X-ray diffractometer manufactured by Rigaku Co., Ltd.) and using a Cu tube ball and Kβ filter method to scan with a scanning range of 2θ / θ, the X-ray diffraction peak intensities (intensities of X-ray diffraction peaks) of the (111) plane, (200) plane, (220) plane and (311) plane of the silver-plated film obtained based on the obtained X-ray diffraction pattern are divided by the respective relative intensity ratios recorded in JCDP Card No. 40783 (relative intensity ratios in powder measurement) ((111):(200):(220):(311)=100:40:25:26) to obtain the corrected value.
[0035] In addition, after the obtained silver-plated material was heated at 350°C for 1 minute, an adhesive tape (transparent tape manufactured by Michelbon Co., Ltd.) was pasted on the surface of the silver-plated material, and a cross-cut tape peeling test was performed in accordance with JIS H8504. The peeling of the silver-plated film was visually evaluated, and the result showed that there was no peeling and the adhesion was good.
[0036] The obtained silver-plated material was heated at 350°C for 1 minute, then bent 180° and bent back, and then visually evaluated for peeling of the silver-plated film. The result showed that there was no peeling and the adhesion was good.
[0037] In addition, two sheets of the above-mentioned silver-plated material were prepared and placed in a constant temperature and humidity chamber (TPAV-48-20 manufactured by Isuzu Corporation) set at a temperature of 85°C and a humidity of 85%. After 240 hours and 500 hours, an adhesive tape (cellophane tape manufactured by Michelbon Co., Ltd.) was attached to the surface of the sample piece, and a cross-cut tape peeling test was performed in accordance with JIS H8504. The presence or absence of peeling of the silver-plated film was visually evaluated. The result showed that there was no peeling and good adhesion after 240 hours, but after 500 hours, the silver-plated film peeled off in an area greater than 10% by area relative to the surface area of the silver-plated film to which the adhesive tape was attached.
[0038] In addition, two sheets of the above-mentioned silver-plated material were prepared and placed in a constant temperature and humidity chamber set at a temperature of 85°C and a humidity of 85%. They were bent 180° and bent back after 240 hours and 500 hours respectively. The silver-plated film at the bent parts (peaks and valleys) was visually evaluated for peeling. The results showed that there was no peeling and good adhesion after 240 hours, but there was peeling after 500 hours.
[0039] [Example 2] In addition to the current density of 2.8A / dm when forming the base silver plating film 2 A silver-plated material was obtained by the same method as in Example 1 except that the plating time was 5 seconds. The thickness of the central portion of the base silver-plated film of the silver-plated material was measured by the fluorescent X-ray film thickness meter and found to be 0.1 μm.
[0040] The silver-plated material thus obtained was subjected to the same method as in Example 1 to measure the Vickers hardness HV, evaluate the wear resistance, and calculate the crystallite size. As a result, the Vickers hardness HV was 136.1 on average. In addition, it was confirmed that the material was not exposed after 400 reciprocating sliding movements, and the wear resistance was excellent, with the maximum value of the dynamic friction coefficient being 0.44. In addition, the average crystallite size was 130.6 angstroms (13.06 nm).
[0041] The above-mentioned silver-plated material was visually evaluated for peeling of the silver-plated film by the same method as in Example 1. The results showed that there was no peeling in any of the cases after heating at 350°C for 1 minute, after heating at 350°C for 1 minute, after being bent 180° tightly and then bent back, after being placed in a constant temperature and humidity chamber for 500 hours, and after being placed in a constant temperature and humidity chamber for 500 hours, after being bent 180° tightly and then bent back, and the adhesion was good.
[0042] [Example 3] In addition to the current density of 7A / dm when forming the base silver plating film 2 A silver-plated material was obtained by the same method as in Example 1 except that the plating time was 4 seconds. The thickness of the central portion of the base silver-plated film of the silver-plated material was measured by the fluorescent X-ray film thickness meter and found to be 0.2 μm.
[0043] The silver-plated material thus obtained was subjected to the same method as in Example 1 to measure the Vickers hardness HV, evaluate the wear resistance, and calculate the crystallite size. As a result, the Vickers hardness HV was 132.1 on average. In addition, it was confirmed that the material was not exposed after 400 reciprocating sliding movements, and the wear resistance was excellent, with the maximum value of the dynamic friction coefficient being 0.46. In addition, the average crystallite size was 118.8 angstroms (11.88 nm).
[0044] The above-mentioned silver-plated material was visually evaluated for peeling of the silver-plated film by the same method as in Example 1. The results showed that there was no peeling in any of the cases after heating at 350°C for 1 minute, after heating at 350°C for 1 minute, after being bent 180° tightly and then bent back, after being placed in a constant temperature and humidity chamber for 500 hours, and after being placed in a constant temperature and humidity chamber for 500 hours, after being bent 180° tightly and then bent back, and the adhesion was good.
[0045] [Example 4] In addition to the current density of 7A / dm when forming the base silver plating film 2 A silver-plated material was obtained by the same method as in Example 1 except that the electroplating time was 9 seconds. The thickness of the central portion of the base silver-plated film of the silver-plated material was measured by the fluorescent X-ray film thickness meter and found to be 0.5 μm.
[0046] The silver-plated material thus obtained was subjected to the same method as in Example 1 to measure the Vickers hardness HV, evaluate the wear resistance, and calculate the crystallite size. As a result, the Vickers hardness HV was 132.4 on average. In addition, it was confirmed that the material was not exposed after 200 reciprocating sliding movements, and the wear resistance was excellent, with the maximum value of the dynamic friction coefficient being 0.34. In addition, the average crystallite size was 133.7 angstroms (13.37 nm).
[0047] The above-mentioned silver-plated material was visually evaluated for peeling of the silver-plated film by the same method as in Example 1. The results showed that there was no peeling in any of the cases after heating at 350°C for 1 minute, after heating at 350°C for 1 minute, after being bent 180° tightly and then bent back, after being placed in a constant temperature and humidity chamber for 500 hours, and after being placed in a constant temperature and humidity chamber for 500 hours, after being bent 180° tightly and then bent back, and the adhesion was good.
[0048] [Example 5] In addition to the current density of 7A / dm when forming the base silver plating film 2 A silver-plated material was obtained by the same method as in Example 1 except that the plating time was 18 seconds. The thickness of the central portion of the base silver-plated film of the silver-plated material was measured by the fluorescent X-ray film thickness meter and found to be 1.0 μm.
[0049] The silver-plated material thus obtained was subjected to the same method as in Example 1 to measure the Vickers hardness HV, evaluate the wear resistance, and calculate the crystallite size. As a result, the Vickers hardness HV was 124.1 on average. In addition, it was confirmed that the material was not exposed after 300 reciprocating sliding movements, and the wear resistance was excellent, with the maximum value of the dynamic friction coefficient being 0.42. In addition, the average crystallite size was 528.1 angstroms (52.81 nm).
[0050] The above-mentioned silver-plated material was visually evaluated for peeling of the silver-plated film by the same method as in Example 1. The results showed that there was no peeling in any of the cases after heating at 350°C for 1 minute, after heating at 350°C for 1 minute, after being bent 180° tightly and then bent back, after being placed in a constant temperature and humidity chamber for 500 hours, and after being placed in a constant temperature and humidity chamber for 500 hours, after being bent 180° tightly and then bent back, and the adhesion was good.
[0051] [Example 6] A silver-plated material was obtained by the same method as in Example 3 except that a silver-plating solution (silver concentration 95 g / L, free cyanide concentration 20 g / L, benzothiazole component (BT) concentration 21 g / L) composed of an aqueous solution containing 175 g / L of potassium silver cyanide (KAg(CN)2), 50 g / L of potassium cyanide (KCN), and 30 g / L of sodium 2-mercaptobenzothiazole (sodium mercaptobenzothiazole (SMBT)) was used as the silver-plating solution used when forming the surface silver-plated film. The thickness of the central portion of the silver-plated film of the silver-plated material (the total thickness of the central portion of the base and surface silver-plated films) was measured with the above-mentioned fluorescent X-ray film thickness meter, and the result was 1.2 μm.
[0052] The silver-plated material thus obtained was evaluated for wear resistance and the crystallite size was calculated in the same manner as in Example 1. As a result, it was confirmed that the raw material was not exposed even after 400 reciprocating sliding movements, the wear resistance was excellent, and the maximum value of the dynamic friction coefficient was 0.36. In addition, the average crystallite size was 139.5 angstroms (13.95 nm).
[0053] The above-mentioned silver-plated material was visually evaluated for peeling of the silver-plated film by the same method as in Example 1. The results showed that there was no peeling in any of the cases after heating at 350°C for 1 minute, after heating at 350°C for 1 minute, after being bent 180° tightly and then bent back, after being placed in a constant temperature and humidity chamber for 500 hours, and after being placed in a constant temperature and humidity chamber for 500 hours, after being bent 180° tightly and then bent back, and the adhesion was good.
[0054] [Example 7] A silver-plated material was obtained by the same method as in Example 3 except that a silver-plating solution (silver concentration 95 g / L, free cyanide concentration 24 g / L, benzothiazole component (BT) concentration 21 g / L) composed of an aqueous solution containing 175 g / L of potassium silver cyanide (KAg(CN)2), 60 g / L of potassium cyanide (KCN), and 30 g / L of sodium 2-mercaptobenzothiazole (sodium mercaptobenzothiazole (SMBT)) was used as the silver-plating solution used when forming the surface silver-plated film. The thickness of the central portion of the silver-plated film of the silver-plated material (the total thickness of the central portion of the silver-plated film of the base and the surface layer) was measured with the above-mentioned fluorescent X-ray film thickness meter, and the result was 1.2 μm.
[0055] The silver-plated material thus obtained was evaluated for wear resistance and the crystallite size was calculated in the same manner as in Example 1. As a result, it was confirmed that the raw material was not exposed even after 500 reciprocating sliding movements, the wear resistance was excellent, and the maximum value of the dynamic friction coefficient was 0.38. In addition, the average crystallite size was 128.9 angstroms (12.89 nm).
[0056] The above-mentioned silver-plated material was visually evaluated for peeling of the silver-plated film by the same method as in Example 1. The results showed that there was no peeling in any of the cases after heating at 350°C for 1 minute, after heating at 350°C for 1 minute, after being bent 180° tightly and then bent back, after being placed in a constant temperature and humidity chamber for 500 hours, and after being placed in a constant temperature and humidity chamber for 500 hours, after being bent 180° tightly and then bent back, and the adhesion was good.
[0057] [Example 8] A silver-plated material was obtained by the same method as in Example 3 except that a silver-plating solution (silver concentration 95 g / L, free cyanide concentration 28 g / L, benzothiazole component (BT) concentration 21 g / L) composed of an aqueous solution containing 175 g / L of potassium silver cyanide (KAg(CN)2), 70 g / L of potassium cyanide (KCN), and 30 g / L of sodium 2-mercaptobenzothiazole (sodium mercaptobenzothiazole (SMBT)) was used as the silver-plating solution used when forming the surface silver-plated film. The thickness of the central portion of the silver-plated film of the silver-plated material (the total thickness of the central portion of the base and surface silver-plated films) was measured with the above-mentioned fluorescent X-ray film thickness meter and the result was 1.2 μm.
[0058] The silver-plated material thus obtained was evaluated for wear resistance and the crystallite size was calculated in the same manner as in Example 1. As a result, it was confirmed that the material was not exposed even after 200 reciprocating sliding movements, and the wear resistance was excellent, with the maximum value of the dynamic friction coefficient being 0.37. In addition, the average crystallite size was 129.7 angstroms (12.97 nm).
[0059] The above-mentioned silver-plated material was visually evaluated for peeling of the silver-plated film by the same method as in Example 1. The results showed that there was no peeling in any of the cases after heating at 350°C for 1 minute, after heating at 350°C for 1 minute, after being bent 180° tightly and then bent back, after being placed in a constant temperature and humidity chamber for 500 hours, and after being placed in a constant temperature and humidity chamber for 500 hours, after being bent 180° tightly and then bent back, and the adhesion was good.
[0060] [Example 9] A silver-plated material was obtained by the same method as in Example 3 except that a silver-plating solution (silver concentration 95 g / L, free cyanide concentration 32 g / L, benzothiazole component (BT) concentration 21 g / L) composed of an aqueous solution containing 175 g / L of potassium silver cyanide (KAg(CN)2), 80 g / L of potassium cyanide (KCN), and 30 g / L of sodium 2-mercaptobenzothiazole (sodium mercaptobenzothiazole (SMBT)) was used as the silver-plating solution used when forming the surface silver-plated film. The thickness of the central portion of the silver-plated film of the silver-plated material (the total thickness of the central portion of the base and surface silver-plated films) was measured with the above-mentioned fluorescent X-ray film thickness meter, and the result was 1.2 μm.
[0061] The silver-plated material thus obtained was evaluated for wear resistance and the crystallite size was calculated in the same manner as in Example 1. As a result, it was confirmed that the material was not exposed even after 300 reciprocating sliding movements, and the wear resistance was excellent, with the maximum value of the dynamic friction coefficient being 0.40. The average crystallite size was 132.6 angstroms (13.26 nm).
[0062] The above-mentioned silver-plated material was visually evaluated for peeling of the silver-plated film by the same method as in Example 1. The results showed that there was no peeling in any of the cases after heating at 350°C for 1 minute, after heating at 350°C for 1 minute, after being bent 180° tightly and then bent back, after being placed in a constant temperature and humidity chamber for 500 hours, and after being placed in a constant temperature and humidity chamber for 500 hours, after being bent 180° tightly and then bent back, and the adhesion was good.
[0063] [Example 10] A silver-plated material was obtained by the same method as in Example 3 except that a silver-plating solution (silver concentration 95 g / L, free cyanide concentration 36 g / L, benzothiazole component (BT) concentration 21 g / L) composed of an aqueous solution containing 175 g / L of potassium silver cyanide (KAg(CN)2), 90 g / L of potassium cyanide (KCN), and 30 g / L of sodium 2-mercaptobenzothiazole (sodium mercaptobenzothiazole (SMBT)) was used as the silver-plating solution used when forming the surface silver-plated film. The thickness of the central portion of the silver-plated film of the silver-plated material (the total thickness of the central portion of the base and surface silver-plated films) was measured with the above-mentioned fluorescent X-ray film thickness meter, and the result was 1.2 μm.
[0064] The silver-plated material thus obtained was evaluated for wear resistance and the crystallite size was calculated in the same manner as in Example 1. As a result, it was confirmed that the raw material was not exposed even after 500 reciprocating sliding movements, the wear resistance was excellent, and the maximum value of the dynamic friction coefficient was 0.43. The average crystallite size was 135.0 angstroms (13.50 nm).
[0065] The above-mentioned silver-plated material was visually evaluated for peeling of the silver-plated film by the same method as in Example 1. The results showed that there was no peeling in any of the cases after heating at 350°C for 1 minute, after heating at 350°C for 1 minute, after being bent 180° tightly and then bent back, after being placed in a constant temperature and humidity chamber for 500 hours, and after being placed in a constant temperature and humidity chamber for 500 hours, after being bent 180° tightly and then bent back, and the adhesion was good.
[0066] [Example 11] A silver-plated material was obtained by the same method as in Example 3 except that a silver-plating solution (silver concentration 95 g / L, free cyanide concentration 40 g / L, benzothiazole component (BT) concentration 21 g / L) composed of an aqueous solution containing 175 g / L of potassium silver cyanide (KAg(CN)2), 100 g / L of potassium cyanide (KCN), and 30 g / L of sodium 2-mercaptobenzothiazole (sodium mercaptobenzothiazole (SMBT)) was used as the silver-plating solution used when forming the surface silver-plated film. The thickness of the central portion of the silver-plated film of the silver-plated material (the total thickness of the central portion of the base and surface silver-plated films) was measured with the above-mentioned fluorescent X-ray film thickness meter and the result was 1.2 μm.
[0067] The silver-plated material thus obtained was evaluated for wear resistance and the crystallite size was calculated in the same manner as in Example 1. As a result, it was confirmed that the material was not exposed even after 300 reciprocating sliding movements, and the wear resistance was excellent, with the maximum value of the dynamic friction coefficient being 0.39. In addition, the average crystallite size was 134.0 angstroms (13.40 nm).
[0068] The above-mentioned silver-plated material was visually evaluated for peeling of the silver-plated film by the same method as in Example 1. The results showed that there was no peeling in any of the cases after heating at 350°C for 1 minute, after heating at 350°C for 1 minute, after being bent 180° tightly and then bent back, after being placed in a constant temperature and humidity chamber for 500 hours, and after being placed in a constant temperature and humidity chamber for 500 hours, after being bent 180° tightly and then bent back, and the adhesion was good.
[0069] [Example 12] A silver-plated material was obtained by the same method as in Example 3 except that a silver-plating solution (silver concentration 95 g / L, free cyanide concentration 44 g / L, benzothiazole component (BT) concentration 21 g / L) composed of an aqueous solution containing 175 g / L of potassium silver cyanide (KAg(CN)2), 110 g / L of potassium cyanide (KCN), and 30 g / L of sodium 2-mercaptobenzothiazole (sodium mercaptobenzothiazole (SMBT)) was used as the silver-plating solution used when forming the surface silver-plated film. The thickness of the central portion of the silver-plated film of the silver-plated material (the total thickness of the central portion of the base and surface silver-plated films) was measured with the above-mentioned fluorescent X-ray film thickness meter and the result was 1.2 μm.
[0070] The silver-plated material thus obtained was evaluated for wear resistance and the crystallite size was calculated in the same manner as in Example 1. As a result, it was confirmed that the raw material was not exposed even after 400 reciprocating sliding movements, the wear resistance was excellent, and the maximum value of the dynamic friction coefficient was 0.42. The average crystallite size was 148.7 angstroms (14.87 nm).
[0071] The above-mentioned silver-plated material was visually evaluated for peeling of the silver-plated film by the same method as in Example 1. The results showed that there was no peeling in any of the cases after heating at 350°C for 1 minute, after heating at 350°C for 1 minute, after being bent 180° tightly and then bent back, after being placed in a constant temperature and humidity chamber for 500 hours, and after being placed in a constant temperature and humidity chamber for 500 hours, after being bent 180° tightly and then bent back, and the adhesion was good.
[0072] [Example 13] A silver-plated material was obtained by the same method as in Example 3 except that a silver-plating solution (silver concentration 95 g / L, free cyanide concentration 48 g / L, benzothiazole component (BT) concentration 21 g / L) composed of an aqueous solution containing 175 g / L of potassium silver cyanide (KAg(CN)2), 120 g / L of potassium cyanide (KCN), and 30 g / L of sodium 2-mercaptobenzothiazole (sodium mercaptobenzothiazole (SMBT)) was used as the silver-plating solution used when forming the surface silver-plated film. The thickness of the central portion of the silver-plated film of the silver-plated material (the total thickness of the central portion of the base and surface silver-plated films) was measured with the above-mentioned fluorescent X-ray film thickness meter, and the result was 1.2 μm.
[0073] The silver-plated material thus obtained was evaluated for wear resistance and the crystallite size was calculated in the same manner as in Example 1. As a result, it was confirmed that the raw material was not exposed even after 400 reciprocating sliding movements, the wear resistance was excellent, and the maximum value of the dynamic friction coefficient was 0.41. The average crystallite size was 142.3 angstroms (14.23 nm).
[0074] The above-mentioned silver-plated material was visually evaluated for peeling of the silver-plated film by the same method as in Example 1. The results showed that there was no peeling after heating at 350°C for 1 minute, after heating at 350°C for 1 minute and then bending 180° tightly, after placing in a constant temperature and humidity chamber for 500 hours, and after placing in a constant temperature and humidity chamber set to a humidity of 85% and then bending 180° tightly after 500 hours, and the adhesion was good.
[0075] [Example 14] A silver-plated material was obtained by the same method as in Example 3 except that a silver-plating solution (silver concentration 95 g / L, free cyanide concentration 52 g / L, benzothiazole component (BT) concentration 21 g / L) composed of an aqueous solution containing 175 g / L of potassium silver cyanide (KAg(CN)2), 130 g / L of potassium cyanide (KCN), and 30 g / L of sodium 2-mercaptobenzothiazole (sodium mercaptobenzothiazole (SMBT)) was used as the silver-plating solution used when forming the surface silver-plated film. The thickness of the central portion of the silver-plated film of the silver-plated material (the total thickness of the central portion of the base and surface silver-plated films) was measured with the above-mentioned fluorescent X-ray film thickness meter, and the result was 1.2 μm.
[0076] The silver-plated material thus obtained was evaluated for wear resistance and the crystallite size was calculated in the same manner as in Example 1. As a result, it was confirmed that the raw material was not exposed even after 300 reciprocating sliding movements, the wear resistance was excellent, and the maximum value of the dynamic friction coefficient was 0.46. The average crystallite size was 141.0 angstroms (14.10 nm).
[0077] The above-mentioned silver-plated material was visually evaluated for peeling of the silver-plated film by the same method as in Example 1. The results showed that there was no peeling in any of the cases after heating at 350°C for 1 minute, after heating at 350°C for 1 minute, after being bent 180° tightly and then bent back, after being placed in a constant temperature and humidity chamber for 500 hours, and after being placed in a constant temperature and humidity chamber for 500 hours, after being bent 180° tightly and then bent back, and the adhesion was good.
[0078] [Example 15] A silver-plated material was obtained by the same method as in Example 3 except that a silver-plating solution (silver concentration 95 g / L, free cyanide concentration 36 g / L, benzothiazole component (BT) concentration 14 g / L) composed of an aqueous solution containing 175 g / L of potassium silver cyanide (KAg(CN)2), 90 g / L of potassium cyanide (KCN), and 20 g / L of sodium 2-mercaptobenzothiazole (sodium mercaptobenzothiazole (SMBT)) was used as the silver-plating solution used when forming the surface silver-plated film. The thickness of the central portion of the silver-plated film of the silver-plated material (the total thickness of the central portion of the base and surface silver-plated films) was measured with the above-mentioned fluorescent X-ray film thickness meter, and the result was 1.2 μm.
[0079] The silver-plated material thus obtained was evaluated for wear resistance and the crystallite size was calculated in the same manner as in Example 1. As a result, it was confirmed that the raw material was not exposed even after 100 reciprocating sliding movements, the wear resistance was excellent, and the maximum value of the dynamic friction coefficient was 0.52. In addition, the average crystallite size was 135.7 angstroms (13.57 nm).
[0080] The above-mentioned silver-plated material was visually evaluated for peeling of the silver-plated film by the same method as in Example 1. The results showed that there was no peeling in any of the cases after heating at 350°C for 1 minute, after heating at 350°C for 1 minute, after being bent 180° tightly and then bent back, after being placed in a constant temperature and humidity chamber for 500 hours, and after being placed in a constant temperature and humidity chamber for 500 hours, after being bent 180° tightly and then bent back, and the adhesion was good.
[0081] [Example 16] A silver-plated material was obtained by the same method as in Example 3 except that a silver-plating solution (silver concentration 95 g / L, free cyanide concentration 36 g / L, benzothiazole component (BT) concentration 18 g / L) composed of an aqueous solution containing 175 g / L of potassium silver cyanide (KAg(CN)2), 90 g / L of potassium cyanide (KCN), and 25 g / L of sodium 2-mercaptobenzothiazole (sodium mercaptobenzothiazole (SMBT)) was used as the silver-plating solution used for forming the surface silver-plated film. The thickness of the central portion of the silver-plated film of the silver-plated material (the total thickness of the central portion of the base and surface silver-plated films) was measured with the above-mentioned fluorescent X-ray film thickness meter, and the result was 1.2 μm.
[0082] The silver-plated material thus obtained was evaluated for wear resistance and the crystallite size was calculated in the same manner as in Example 1. As a result, it was confirmed that the raw material was not exposed even after 400 reciprocating sliding movements, the wear resistance was excellent, and the maximum value of the dynamic friction coefficient was 0.49. In addition, the average crystallite size was 134.0 angstroms (13.40 nm).
[0083] The above-mentioned silver-plated material was visually evaluated for peeling of the silver-plated film by the same method as in Example 1. The results showed that there was no peeling in any of the cases after heating at 350°C for 1 minute, after heating at 350°C for 1 minute, after being bent 180° tightly and then bent back, after being placed in a constant temperature and humidity chamber for 500 hours, and after being placed in a constant temperature and humidity chamber for 500 hours, after being bent 180° tightly and then bent back, and the adhesion was good.
[0084] [Example 17] A silver-plated material was obtained by the same method as in Example 3 except that a silver-plating solution (silver concentration 95 g / L, free cyanide concentration 36 g / L, benzothiazole component (BT) concentration 25 g / L) composed of an aqueous solution containing 175 g / L of potassium silver cyanide (KAg(CN)2), 90 g / L of potassium cyanide (KCN), and 35 g / L of sodium 2-mercaptobenzothiazole (sodium mercaptobenzothiazole (SMBT)) was used as the silver-plating solution used when forming the surface silver-plated film. The thickness of the central portion of the silver-plated film of the silver-plated material (the total thickness of the central portion of the base and surface silver-plated films) was measured with the above-mentioned fluorescent X-ray film thickness meter, and the result was 1.2 μm.
[0085] The silver-plated material thus obtained was evaluated for wear resistance and the crystallite size was calculated in the same manner as in Example 1. As a result, it was confirmed that the raw material was not exposed even after 500 reciprocating sliding movements, the wear resistance was excellent, and the maximum value of the dynamic friction coefficient was 0.40. In addition, the average crystallite size was 115.3 angstroms (11.53 nm).
[0086] The above-mentioned silver-plated material was visually evaluated for peeling of the silver-plated film by the same method as in Example 1. The results showed that there was no peeling in any of the cases after heating at 350°C for 1 minute, after heating at 350°C for 1 minute, after being bent 180° tightly and then bent back, after being placed in a constant temperature and humidity chamber for 500 hours, and after being placed in a constant temperature and humidity chamber for 500 hours, after being bent 180° tightly and then bent back, and the adhesion was good.
[0087] [Example 18] A silver-plated material was obtained by the same method as in Example 3 except that a silver-plating solution (silver concentration 95 g / L, free cyanide concentration 36 g / L, benzothiazole component (BT) concentration 29 g / L) composed of an aqueous solution containing 175 g / L of potassium silver cyanide (KAg(CN)2), 90 g / L of potassium cyanide (KCN), and 40 g / L of sodium 2-mercaptobenzothiazole (sodium mercaptobenzothiazole (SMBT)) was used as the silver-plating solution used when forming the surface silver-plated film. The thickness of the central portion of the silver-plated film of the silver-plated material (the total thickness of the central portion of the base and surface silver-plated films) was measured with the above-mentioned fluorescent X-ray film thickness meter, and the result was 1.2 μm.
[0088] The silver-plated material thus obtained was evaluated for wear resistance and the crystallite size was calculated in the same manner as in Example 1. As a result, it was confirmed that the material was not exposed even after 700 reciprocating sliding movements, and the wear resistance was excellent, with the maximum value of the dynamic friction coefficient being 0.42. In addition, the average crystallite size was 102.1 angstroms (10.21 nm).
[0089] The above-mentioned silver-plated material was visually evaluated for peeling of the silver-plated film by the same method as in Example 1. The results showed that there was no peeling in any of the cases after heating at 350°C for 1 minute, after heating at 350°C for 1 minute, after being bent 180° tightly and then bent back, after being placed in a constant temperature and humidity chamber for 500 hours, and after being placed in a constant temperature and humidity chamber for 500 hours, after being bent 180° tightly and then bent back, and the adhesion was good.
[0090] [Example 19] A silver-plated material was obtained by the same method as in Example 3 except that a silver-plating solution (silver concentration 95 g / L, free cyanide concentration 36 g / L, benzothiazole component (BT) concentration 36 g / L) composed of an aqueous solution containing 175 g / L of potassium silver cyanide (KAg(CN)2), 90 g / L of potassium cyanide (KCN), and 50 g / L of sodium 2-mercaptobenzothiazole (sodium mercaptobenzothiazole (SMBT)) was used as the silver-plating solution used when forming the surface silver-plated film. The thickness of the central portion of the silver-plated film of the silver-plated material (the total thickness of the central portion of the base and surface silver-plated films) was measured with the above-mentioned fluorescent X-ray film thickness meter, and the result was 1.2 μm.
[0091] The silver-plated material thus obtained was evaluated for wear resistance and the crystallite size was calculated in the same manner as in Example 1. As a result, it was confirmed that the material was not exposed even after more than 1,000 reciprocating sliding movements, and that the wear resistance was excellent, with the maximum value of the dynamic friction coefficient being 0.52. In addition, the average crystallite size was 109.9 angstroms (10.99 nm).
[0092] The above-mentioned silver-plated material was visually evaluated for peeling of the silver-plated film by the same method as in Example 1. The results showed that there was no peeling in any of the cases after heating at 350°C for 1 minute, after heating at 350°C for 1 minute, after being bent 180° tightly and then bent back, after being placed in a constant temperature and humidity chamber for 500 hours, and after being placed in a constant temperature and humidity chamber for 500 hours, after being bent 180° tightly and then bent back, and the adhesion was good.
[0093] [Example 20] A silver-plated material was obtained by the same method as in Example 3 except that a silver-plating solution (silver concentration 95 g / L, free cyanide concentration 36 g / L, benzothiazole component (BT) concentration 43 g / L) composed of an aqueous solution containing 175 g / L of potassium silver cyanide (KAg(CN)2), 90 g / L of potassium cyanide (KCN), and 60 g / L of sodium 2-mercaptobenzothiazole (sodium mercaptobenzothiazole (SMBT)) was used as the silver-plating solution used when forming the surface silver-plated film. The thickness of the central portion of the silver-plated film of the silver-plated material (the total thickness of the central portion of the base and surface silver-plated films) was measured with the above-mentioned fluorescent X-ray film thickness meter, and the result was 1.2 μm.
[0094] The silver-plated material thus obtained was evaluated for wear resistance and the crystallite size was calculated in the same manner as in Example 1. As a result, it was confirmed that the material was not exposed even after more than 1,000 reciprocating sliding movements, and that the wear resistance was excellent, with the maximum value of the dynamic friction coefficient being 0.54. In addition, the average crystallite size was 126.6 angstroms (12.66 nm).
[0095] The above-mentioned silver-plated material was visually evaluated for peeling of the silver-plated film by the same method as in Example 1. The results showed that there was no peeling in any of the cases after heating at 350°C for 1 minute, after heating at 350°C for 1 minute, after being bent 180° tightly and then bent back, after being placed in a constant temperature and humidity chamber for 500 hours, and after being placed in a constant temperature and humidity chamber for 500 hours, after being bent 180° tightly and then bent back, and the adhesion was good.
[0096] [Example 21] A silver-plated material was obtained by the same method as in Example 3 except that a silver-plating solution (silver concentration 95 g / L, free cyanide concentration 36 g / L, benzothiazole component (BT) concentration 50 g / L) composed of an aqueous solution containing 175 g / L of potassium silver cyanide (KAg(CN)2), 90 g / L of potassium cyanide (KCN), and 70 g / L of sodium 2-mercaptobenzothiazole (sodium mercaptobenzothiazole (SMBT)) was used as the silver-plating solution used for forming the surface silver-plated film. The thickness of the central portion of the silver-plated film of the silver-plated material (the total thickness of the central portion of the base and surface silver-plated films) was measured with the above-mentioned fluorescent X-ray film thickness meter and the result was 1.2 μm.
[0097] The silver-plated material thus obtained was evaluated for wear resistance and the crystallite size was calculated in the same manner as in Example 1. As a result, it was confirmed that the material was not exposed even after more than 1,000 reciprocating sliding movements, and that the wear resistance was excellent, with the maximum value of the dynamic friction coefficient being 0.57. In addition, the average crystallite size was 128.1 angstroms (12.81 nm).
[0098] The above-mentioned silver-plated material was visually evaluated for peeling of the silver-plated film by the same method as in Example 1. The results showed that there was no peeling in any of the cases after heating at 350°C for 1 minute, after heating at 350°C for 1 minute, after being bent 180° tightly and then bent back, after being placed in a constant temperature and humidity chamber for 500 hours, and after being placed in a constant temperature and humidity chamber for 500 hours, after being bent 180° tightly and then bent back, and the adhesion was good.
[0099] [Example 22] In addition to the current density of 7A / dm when forming the base silver plating film 2 A silver-plated material was obtained by the same method as in Example 1 except that the electroplating time was 36 seconds. The thickness of the central portion of the base silver-plated film of the silver-plated material was measured by the fluorescent X-ray film thickness meter and found to be 2 μm.
[0100] The silver-plated material thus obtained was subjected to the same method as in Example 1 to measure the Vickers hardness HV, evaluate the wear resistance, and calculate the crystallite size. As a result, the Vickers hardness HV was 112.3 on average. In addition, it was confirmed that the material was not exposed after 200 reciprocating sliding movements, the wear resistance was excellent, and the maximum value of the dynamic friction coefficient was 0.50. In addition, the average crystallite size was 584.1 angstroms (58.41 nm).
[0101] The above-mentioned silver-plated material was visually evaluated for peeling of the silver-plated film by the same method as in Example 1. The results showed that there was no peeling in any of the cases after heating at 350°C for 1 minute, after heating at 350°C for 1 minute, after being bent 180° tightly and then bent back, after being placed in a constant temperature and humidity chamber for 500 hours, and after being placed in a constant temperature and humidity chamber for 500 hours, after being bent 180° tightly and then bent back, and the adhesion was good.
[0102] [Example 23] In addition to the current density of 7A / dm when forming the base silver plating film 2 A silver-plated material was obtained by the same method as in Example 1 except that the plating time was 90 seconds. The thickness of the central portion of the base silver-plated film of the silver-plated material was measured by the fluorescent X-ray film thickness meter and found to be 5 μm.
[0103] The silver-plated material thus obtained was subjected to the same method as in Example 1 to measure the Vickers hardness HV, evaluate the wear resistance, and calculate the crystallite size. As a result, the Vickers hardness HV was 96.8 on average. In addition, it was confirmed that the material was not exposed after 400 reciprocating sliding movements, and the wear resistance was excellent, with the maximum value of the dynamic friction coefficient being 0.52. In addition, the average crystallite size was 611.9 angstroms (61.19 nm).
[0104] The above-mentioned silver-plated material was visually evaluated for peeling of the silver-plated film by the same method as in Example 1. The results showed that there was no peeling in any of the cases after heating at 350°C for 1 minute, after heating at 350°C for 1 minute, after being bent 180° tightly and then bent back, after being placed in a constant temperature and humidity chamber for 500 hours, and after being placed in a constant temperature and humidity chamber for 500 hours, after being bent 180° tightly and then bent back, and the adhesion was good.
[0105] [Example 24] In addition to the current density of 7A / dm when forming the base silver plating film 2 A silver-plated material was obtained by the same method as in Example 1 except that the electroplating time was 180 seconds. The thickness of the central portion of the base silver-plated film of the silver-plated material was measured by the fluorescent X-ray film thickness meter and found to be 10 μm.
[0106] The silver-plated material thus obtained was subjected to the same method as in Example 1 to measure the Vickers hardness HV, evaluate the wear resistance, and calculate the crystallite size. As a result, the Vickers hardness HV was 92.0 on average. In addition, it was confirmed that the material was not exposed after 400 reciprocating sliding movements, and the wear resistance was excellent, with the maximum value of the dynamic friction coefficient being 0.50. In addition, the average crystallite size was 625.1 angstroms (62.51 nm).
[0107] The above-mentioned silver-plated material was visually evaluated for peeling of the silver-plated film by the same method as in Example 1. The results showed that there was no peeling in any of the cases after heating at 350°C for 1 minute, after heating at 350°C for 1 minute, after being bent 180° tightly and then bent back, after being placed in a constant temperature and humidity chamber for 500 hours, and after being placed in a constant temperature and humidity chamber for 500 hours, after being bent 180° tightly and then bent back, and the adhesion was good.
[0108] [Comparative Example 1] A silver-plated material was obtained by the same method as in Example 1 except that the base silver-plated film was not formed.
[0109] The silver-plated material thus obtained was subjected to the same method as in Example 1 to measure the Vickers hardness HV, evaluate the wear resistance, and calculate the crystallite size. As a result, the Vickers hardness HV was 139.4 on average. In addition, it was confirmed that the material was not exposed after 400 reciprocating sliding movements, and the wear resistance was excellent, with the maximum value of the dynamic friction coefficient being 0.41. In addition, the average crystallite size was 146.3 angstroms (14.63 nm).
[0110] The above silver-plated material was visually evaluated for peeling of the silver-plated film by the same method as in Example 1. The results showed that there was no peeling after heating at 350°C for 1 minute and after heating at 350°C for 1 minute, followed by 180° close bending and bending back, indicating good adhesion. However, after being placed in a constant temperature and humidity chamber for 240 hours, the silver-plated film peeled off at an area greater than 5% by area relative to the surface area of the impact silver-plated film, and after being placed in a constant temperature and humidity chamber for 500 hours, the silver-plated film peeled off at an area greater than 10% by area relative to the surface area of the impact silver-plated film, indicating poor adhesion. Furthermore, the silver-plated film peeled off after being placed in a constant temperature and humidity chamber for 240 hours, followed by 180° close bending and bending back, and after being placed in a constant temperature and humidity chamber for 500 hours, indicating poor adhesion.
[0111] [Comparative Example 2] Without forming a base silver-plated film, in a silver-plating solution (silver concentration 95 g / L, free cyanide concentration 38 g / L, selenium concentration 69 mg / L) consisting of an aqueous solution containing 175 g / L potassium silver cyanide (KAg(CN)2), 95 g / L potassium cyanide (KCN) and 69 mg / L selenium (Se), the plated material having an impact silver-plated film was used as a cathode and the silver electrode plate was used as an anode. The silver-plated film was stirred at 500 rpm with a stirrer at a current density of 5 A / dm at a liquid temperature of 18°C. 2 A silver-plated material was obtained by the same method as in Example 1 except that the silver-plated film was formed by electroplating (silver plating) for 120 seconds. The thickness of the central portion of the silver-plated film was measured with the fluorescent X-ray film thickness meter and found to be 5 μm.
[0112] The silver-plated material thus obtained was subjected to the same method as in Example 1 to measure the Vickers hardness HV, evaluate the wear resistance, and calculate the crystallite size. As a result, the Vickers hardness HV was 132.0 on average. In addition, it was confirmed that the material was exposed after 80 reciprocating sliding movements, the wear resistance was poor, and the maximum value of the dynamic friction coefficient was 1.71. In addition, the average crystallite size was 278.0 angstroms (27.80 nm).
[0113] The above-mentioned silver-plated material was visually evaluated for peeling of the silver-plated film by the same method as in Example 1. The results showed that there was no peeling in any of the cases after heating at 350°C for 1 minute, after heating at 350°C for 1 minute, after being bent 180° tightly and then bent back, after being placed in a constant temperature and humidity chamber for 500 hours, and after being placed in a constant temperature and humidity chamber for 500 hours, after being bent 180° tightly and then bent back, and the adhesion was good.
[0114] [Example 25] A silver-plated material was obtained by the same method as in Example 3 except that a silver-plating solution (silver concentration 75 g / L, free cyanide concentration 32 g / L, benzothiazole component (BT) concentration 23 g / L) composed of an aqueous solution containing 138 g / L of potassium silver cyanide (KAg(CN)2), 80 g / L of potassium cyanide (KCN), and 32 g / L of sodium 2-mercaptobenzothiazole (sodium mercaptobenzothiazole (SMBT)) was used as the silver-plating solution used when forming the surface silver-plated film. The thickness of the central portion of the silver-plated film of the silver-plated material (the total thickness of the central portion of the base and surface silver-plated films) was measured with the above-mentioned fluorescent X-ray film thickness meter and the result was 1.2 μm.
[0115] The silver-plated material thus obtained was subjected to the same method as in Example 1 to measure the Vickers hardness HV, evaluate the wear resistance, and calculate the crystallite size. As a result, the Vickers hardness HV was 122.6 on average. In addition, it was confirmed that the material was not exposed after 400 reciprocating sliding movements, and the wear resistance was excellent, with the maximum value of the dynamic friction coefficient being 0.41. The average crystallite size was 116.0 angstroms (11.60 nm).
[0116] The above-mentioned silver-plated material was visually evaluated for peeling of the silver-plated film by the same method as in Example 1. The results showed that there was no peeling in any of the cases after heating at 350°C for 1 minute, after heating at 350°C for 1 minute, after being bent 180° tightly and then bent back, after being placed in a constant temperature and humidity chamber for 500 hours, and after being placed in a constant temperature and humidity chamber for 500 hours, after being bent 180° tightly and then bent back, and the adhesion was good.
[0117] [Example 26] A silver-plated material was obtained by the same method as in Example 3, except that a silver-plating solution (silver concentration 130 g / L, free cyanide concentration 40 g / L, benzothiazole component (BT) concentration 20 g / L) consisting of an aqueous solution of 240 g / L potassium silver cyanide (KAg(CN)2), 100 g / L potassium cyanide (KCN), and 28 g / L sodium 2-mercaptobenzothiazole (sodium mercaptobenzothiazole (SMBT)) was used as the silver-plating solution used when forming the surface silver-plated film. The thickness of the central portion of the silver-plated film of the silver-plated material (the total thickness of the central portion of the base and surface silver-plated films) was measured with the above-mentioned fluorescent X-ray film thickness meter, and the result was 1.2 μm.
[0118] The silver-plated material thus obtained was subjected to the same method as in Example 1 to measure the Vickers hardness HV, evaluate the wear resistance, and calculate the crystallite size. As a result, the Vickers hardness HV was 125.6 on average. In addition, it was confirmed that the material was not exposed after 300 reciprocating sliding movements, and the wear resistance was excellent, with the maximum value of the dynamic friction coefficient being 0.48. The average crystallite size was 132.5 angstroms (13.25 nm).
[0119] The above-mentioned silver-plated material was visually evaluated for peeling of the silver-plated film by the same method as in Example 1. The results showed that there was no peeling in any of the cases after heating at 350°C for 1 minute, after heating at 350°C for 1 minute, after being bent 180° tightly and then bent back, after being placed in a constant temperature and humidity chamber for 500 hours, and after being placed in a constant temperature and humidity chamber for 500 hours, after being bent 180° tightly and then bent back, and the adhesion was good.
[0120] [Example 27] In a silver plating solution (silver concentration 95 g / L, free cyanide concentration 38 g / L, benzothiazole component (BT) concentration 21 g / L) consisting of an aqueous solution containing 175 g / L potassium silver cyanide (KAg(CN)2), 95 g / L potassium cyanide (KCN), and 30 g / L of sodium 2-mercaptobenzothiazole (sodium mercaptobenzothiazole (SMBT)), a base silver-plated film was formed on the plated material as the cathode and a silver electrode plate as the anode. The solution was stirred at 500 rpm with a stirrer and a current density of 7 A / dm was added at a liquid temperature of 35°C. 2 A silver-plated material was obtained by the same method as in Example 3 except that the silver-plated film was formed by electroplating (silver plating) for 54 seconds. The thickness of the central portion of the silver-plated film was measured with the fluorescent X-ray film thickness meter and found to be 3.29 μm.
[0121] The silver-plated material thus obtained was subjected to the same method as in Example 1 to measure the Vickers hardness HV, evaluate the wear resistance, and calculate the crystallite size. As a result, the Vickers hardness HV was 104.3 on average. In addition, it was confirmed that the material was not exposed even after 700 reciprocating sliding movements, and the wear resistance was excellent, with the maximum value of the dynamic friction coefficient being 0.35. In addition, the average crystallite size was 87.1 angstroms (8.71 nm).
[0122] The above-mentioned silver-plated material was visually evaluated for peeling of the silver-plated film by the same method as in Example 1. The results showed that there was no peeling in any of the cases after heating at 350°C for 1 minute, after heating at 350°C for 1 minute, after being bent 180° tightly and then bent back, after being placed in a constant temperature and humidity chamber for 500 hours, and after being placed in a constant temperature and humidity chamber for 500 hours, after being bent 180° tightly and then bent back, and the adhesion was good.
[0123] [Example 28] In a silver plating solution (silver concentration 95 g / L, free cyanide concentration 38 g / L, benzothiazole component (BT) concentration 21 g / L) consisting of an aqueous solution containing 175 g / L potassium silver cyanide (KAg(CN)2), 95 g / L potassium cyanide (KCN), and 30 g / L of sodium 2-mercaptobenzothiazole (sodium mercaptobenzothiazole (SMBT)), a base silver-plated film was formed on the plated material as the cathode and a silver electrode plate as the anode. The mixture was stirred at 500 rpm with a stirrer and the current density was 7 A / dm at 35°C. 2 A silver-plated material was obtained by the same method as in Example 3 except that the silver-plated film was formed by electroplating (silver plating) for 90 seconds. The thickness of the central portion of the silver-plated film was measured with the fluorescent X-ray film thickness meter and found to be 5.34 μm.
[0124] The silver-plated material thus obtained was subjected to the same method as in Example 1 to measure the Vickers hardness HV, evaluate the wear resistance, and calculate the crystallite size. As a result, the Vickers hardness HV was 92.4 on average. In addition, it was confirmed that the material was not exposed after more than 1000 reciprocating sliding movements, and the wear resistance was excellent, with the maximum value of the dynamic friction coefficient being 0.35. In addition, the average crystallite size was 90.39 angstroms (9.039 nm).
[0125] The above-mentioned silver-plated material was visually evaluated for peeling of the silver-plated film by the same method as in Example 1. The results showed that there was no peeling in any of the cases after heating at 350°C for 1 minute, after heating at 350°C for 1 minute, after being bent 180° tightly and then bent back, after being placed in a constant temperature and humidity chamber for 500 hours, and after being placed in a constant temperature and humidity chamber for 500 hours, after being bent 180° tightly and then bent back, and the adhesion was good.
[0126] [Example 29] In a matte nickel plating solution consisting of an aqueous solution containing 540 g / L of nickel sulfamate tetrahydrate, 25 g / L of nickel chloride and 35 g / L of boric acid, the pre-treated material to be plated was used as the cathode and the nickel electrode plate was used as the anode. The plating was stirred at 500 rpm with a stirrer at a current density of 7 A / dm at a liquid temperature of 50°C. 2 A silver-plated material was obtained by the same method as in Example 3 except that electroplating was performed for 7 seconds (matte nickel plating) to form a matte nickel plating film as a base plating film. The thickness of the central portion of the base plating film was measured by the fluorescent X-ray film thickness meter and found to be 0.1 μm.
[0127] The silver-plated material thus obtained was subjected to the same method as in Example 1 to measure the Vickers hardness HV, evaluate the wear resistance, and calculate the crystallite size. As a result, the Vickers hardness HV was 101.8 on average. In addition, it was confirmed that the material was not exposed after 100 reciprocating sliding movements, and the wear resistance was excellent, with the maximum value of the dynamic friction coefficient being 0.39. In addition, the average crystallite size was 102.53 angstroms (10.253 nm).
[0128] The above-mentioned silver-plated material was visually evaluated for peeling of the silver-plated film by the same method as in Example 1. The results showed that there was no peeling in any of the cases after heating at 350°C for 1 minute, after heating at 350°C for 1 minute, after being bent 180° tightly and then bent back, after being placed in a constant temperature and humidity chamber for 500 hours, and after being placed in a constant temperature and humidity chamber for 500 hours, after being bent 180° tightly and then bent back, and the adhesion was good.
[0129] [Example 30] In a matte nickel plating solution consisting of an aqueous solution containing 540 g / L nickel sulfamate tetrahydrate, 25 g / L nickel chloride and 35 g / L boric acid, the pre-treated material to be plated was used as the cathode and the nickel electrode plate was used as the anode. The solution was stirred at 500 rpm with a stirrer and the current density was 7 A / dm at a liquid temperature of 50°C. 2 A silver-plated material was obtained by the same method as in Example 3 except that electroplating (matte nickel plating) was performed for 14 seconds to form a matte nickel plating film as a base plating film. The thickness of the central portion of the base plating film was measured with the fluorescent X-ray film thickness meter and found to be 0.2 μm.
[0130] The silver-plated material thus obtained was subjected to the same method as in Example 1 to measure the Vickers hardness HV, evaluate the wear resistance, and calculate the crystallite size. As a result, the Vickers hardness HV was 102.3 on average. In addition, it was confirmed that the material was not exposed after 100 reciprocating sliding movements, and the wear resistance was excellent, with the maximum value of the dynamic friction coefficient being 0.48. In addition, the average crystallite size was 106.79 angstroms (10.679 nm).
[0131] The above-mentioned silver-plated material was visually evaluated for peeling of the silver-plated film by the same method as in Example 1. The results showed that there was no peeling in any of the cases after heating at 350°C for 1 minute, after heating at 350°C for 1 minute, after being bent 180° tightly and then bent back, after being placed in a constant temperature and humidity chamber for 500 hours, and after being placed in a constant temperature and humidity chamber for 500 hours, after being bent 180° tightly and then bent back, and the adhesion was good.
[0132] [Example 31] In a matte nickel plating solution consisting of an aqueous solution containing 540 g / L nickel sulfamate tetrahydrate, 25 g / L nickel chloride and 35 g / L boric acid, the pre-treated material to be plated was used as the cathode and the nickel electrode plate was used as the anode. The solution was stirred at 500 rpm with a stirrer and the current density was 7 A / dm at a liquid temperature of 50°C. 2 A silver-plated material was obtained by the same method as in Example 3 except that electroplating (matte nickel plating) was performed for 210 seconds to form a matte nickel plating film as a base plating film. The thickness of the central portion of the base plating film was measured with the fluorescent X-ray film thickness meter and found to be 3 μm.
[0133] The silver-plated material thus obtained was evaluated for wear resistance and the crystallite size was calculated in the same manner as in Example 1. As a result, it was confirmed that the raw material was not exposed even after 300 reciprocating sliding movements, the wear resistance was excellent, and the maximum value of the dynamic friction coefficient was 0.51. In addition, the average crystallite size was 157.62 angstroms (15.762 nm).
[0134] The above-mentioned silver-plated material was visually evaluated for peeling of the silver-plated film by the same method as in Example 1. The results showed that there was no peeling in any of the cases after heating at 350°C for 1 minute, after heating at 350°C for 1 minute, after being bent 180° tightly and then bent back, after being placed in a constant temperature and humidity chamber for 500 hours, and after being placed in a constant temperature and humidity chamber for 500 hours, after being bent 180° tightly and then bent back, and the adhesion was good.
[0135] [Example 32] In a matte nickel plating solution consisting of an aqueous solution containing 540 g / L nickel sulfamate tetrahydrate, 25 g / L nickel chloride and 35 g / L boric acid, the pre-treated material to be plated was used as the cathode and the nickel electrode plate was used as the anode. The plating was stirred at 500 rpm with a stirrer at a current density of 7 A / dm at a liquid temperature of 50°C. 2 A silver-plated material was obtained by the same method as in Example 3 except that electroplating (matte nickel plating) was performed for 350 seconds to form a matte nickel plating film as a base plating film. The thickness of the central portion of the base plating film was measured with the fluorescent X-ray film thickness meter and found to be 5 μm.
[0136] The silver-plated material thus obtained was evaluated for wear resistance and the crystallite size was calculated in the same manner as in Example 1. As a result, it was confirmed that the material was not exposed even after 700 reciprocating sliding movements, and the wear resistance was excellent, with the maximum value of the dynamic friction coefficient being 0.43. In addition, the average crystallite size was 175.15 angstroms (17.515 nm).
[0137] The above-mentioned silver-plated material was visually evaluated for peeling of the silver-plated film by the same method as in Example 1. The results showed that there was no peeling in any of the cases after heating at 350°C for 1 minute, after heating at 350°C for 1 minute, after being bent 180° tightly and then bent back, after being placed in a constant temperature and humidity chamber for 500 hours, and after being placed in a constant temperature and humidity chamber for 500 hours, after being bent 180° tightly and then bent back, and the adhesion was good.
[0138] Tables 1 to 4 show the production conditions and properties of the silver-plated materials obtained in these Examples and Comparative Examples.
[0139] Table 1
[0140] Table 2
[0141] Table 3
[0142] Table 4
[0143] In addition, the cross sections of the silver-plated materials obtained in Examples 10, 15, 21 and Comparative Examples 1 and 2 were observed using a scanning electron microscope. Figure 1 and Figure 2 The cross-sections of the silver-plated materials obtained in Example 10 and Comparative Example 1 are shown in scanning electron microscope photographs (SEM images) at 50,000 times magnification. As a result, it was confirmed that the silver-plated materials obtained in Examples 10, 15, and 21 had a base plated film (matte nickel-plated film) 10 formed on the surface of the substrate, a base silver-plated film 12 formed on the base plated film 10, and a surface layer (carbon-and-sulfur-containing silver-plated film) 14 composed of silver containing carbon (C) and sulfur (S) formed on the base silver-plated film 12. In addition, the silver-plated material obtained in Comparative Example 1 had a base plated film (matte nickel-plated film) 10 formed on the surface of the substrate, and a surface layer (carbon-and-sulfur-containing silver-plated film) 14 composed of silver containing carbon (C) and sulfur (S) formed on the base plated film 10. In addition, the silver-plated material obtained in Comparative Example 2 has a surface layer composed of silver containing a trace amount of selenium (Se) (a silver-plated film containing a trace amount of selenium) instead of the surface layer (a silver-plated film containing carbon and sulfur) 14 composed of silver containing carbon (C) and sulfur (S) of the silver-plated material obtained in Comparative Example 1.
[0144] In addition, the silver-plated materials obtained in Examples 10, 15, 21, 25 and 26 were measured by X-ray photoelectron spectroscopy (XPS) to obtain a depth distribution diagram (showing the results of composition analysis in the depth direction from the outermost surface).
[0145] As a result, in the central part in the thickness direction of the surface layer 14 composed of silver containing carbon and sulfur, the Ag atomic concentration is less than 95at% (89.3at% in Example 10, 92.7at% in Example 15, 83.6at% in Example 21, 85.0at% in Example 25, and 92.6at% in Example 26), the S atomic concentration is greater than 0.6at% (1.3at% in Example 10, 0.8at% in Example 15, 2.5at% in Example 21, 1.8at% in Example 25, and 1.0at% in Example 26), and the ratio of the C atomic concentration to the Ag atomic concentration is greater than 3% (9.7% in Example 10, 6.3% in Example 15, 14.1% in Example 21, 13.9% in Example 25, and 6.4% in Example 26). Furthermore, Se was not detected in any of the samples (Se atomic concentration was less than 0.014 at % (0.01 mass %)).
[0146] On the other hand, in the central portion in the thickness direction of the base silver-plated film 12, the Ag atomic concentration was higher than 95 at% (98.5 at% in Example 10, 97.3 at% in Example 15, 98.5 at% in Example 21, 97.1 at% in Example 25, and 98.4 at% in Example 26), the S atomic concentration was lower than 0.6 at% (0.5 at% in Example 10, 0.3 at% in Example 15, 0.2 at% in Example 21, 0.2 at% in Example 25, and 0.2 at% in Example 26), and the ratio of the C atomic concentration to the Ag atomic concentration was lower than 3% (0.4% in Example 10, 1.3% in Example 15, 0.6% in Example 21, 1.2% in Example 25, and 0.8% in Example 26). Furthermore, Se was not detected (Se atomic concentration was lower than 0.014 at% (0.01 mass%)).
[0147] In addition, the silver-plated materials obtained in Comparative Examples 1 and 2 were measured based on X-ray photoelectron spectroscopy (XPS) to obtain a depth distribution diagram (showing the results of composition analysis from the outermost surface along the depth direction). The results showed that in the central part of the thickness direction of the surface layer 14 composed of silver, the Ag atomic concentration was 90.2at% in Comparative Example 1 and 99.6at% in Comparative Example 2, the S atomic concentration was 1.2at% in Comparative Example 1 and 0.0at% in Comparative Example 2, and the ratio of the C atomic concentration to the Ag atomic concentration was 8.8% in Comparative Example 1 and 0.3% in Comparative Example 2.
[0148] In the measurement based on X-ray photoelectron spectroscopy (XPS), the concentration of C, O, S, Ag, K, Ni, and N as the designated elements was analyzed using an X-ray photoelectron spectroscopy analyzer (PHI5000VersaProbeIII manufactured by Alvac Fiber Co., Ltd.) to investigate the structure of the silver-plated material. The measurement based on X-ray photoelectron spectroscopy (XPS) was performed under the following conditions as the X-ray irradiation conditions: the vacuum degree was 10 -7 Pa, the excitation source is monochromated AlKα, the output power is 25W, the acceleration voltage is 15kV, the beam size is 100μmΦ, the incident angle is 90deg, and the electron beam is irradiated with an electron neutralization gun with an emission current of 20μA, a bias voltage of 1.0V, and an acceleration voltage of 30.0V. At the same time, an argon gun is used to irradiate the electron beam with Ar + The ion species was irradiated with argon ions at an acceleration voltage of 0.11 kV and an emission current of 7 mA, and the photoelectron extraction angle was 45 degrees, the accumulation number was 5 times, the integration time was 40 ms (20 ms×2), the path energy was 140 eV, and the measurement energy interval was 0.25 eV / step.
[0149] In addition, the depth distribution map was obtained by using an argon gun with Ar + Ion sputtering was performed with an acceleration voltage of 4 kV, an emission current of 20 mA, and a scanning area of 2.7 mm×2.7 mm for ion species, and surface etching (for analysis in the depth direction) was performed. This surface etching and measurement based on X-ray photoelectron spectroscopy (XPS) were repeated alternately.
[0150] In addition, in the depth distribution diagram, the peak value of the 3d orbital binding energy of Ag (Ag3d) is 362.0~382.0eV, the peak value of the 1s orbital binding energy of C (C1s) is 278.0~308.0eV, and the peak value of the 2p orbital binding energy of S (S2p) is 156~170eV. The concentrations of Ag, C and S atoms are calculated from these peak values.
[0151] In addition, in order to investigate the binding state of S in the silver-plated materials obtained in Examples 25 and 26, the same X-ray photoelectron spectroscopy (XPS measurement) as described above was performed, except that C was measured with a cumulative number of 10 times, an integration time of 80 ms (20 ms×4), a path energy of 69 eV, and a measurement energy interval of 0.1250 eV / step, and S was measured in the range of 155.0 to 175.0 eV, a cumulative number of 15 times, an integration time of 80 ms (20 ms×4), a path energy of 69 eV, and a measurement energy interval of 0.1250 eV / step.
[0152] As a result, the peaks of the 2p orbital binding energy (S2p) of S were observed in the three ranges of 160.4 to 161.4 eV, 161.6 to 162.9 eV, and 163.2 to 164.5 eV for the silver-plated materials obtained in Examples 25 and 26. In addition, when the silver-plated layer containing SMBT was measured by X-ray photoelectron spectroscopy (XPS), the peaks of the 2p orbital binding energy (S2p) of S were observed in the above three ranges. Therefore, for the silver-plated materials obtained in Examples 25 and 26, the peaks in the range of 161.6 to 162.9 eV in the measurement based on X-ray photoelectron spectroscopy (XPS) were considered to be the peaks of the S atoms derived from the mercapto group of SMBT, the peaks in the range of 163.2 to 164.5 eV were considered to be the peaks derived from the S atoms of the five-membered ring of SMBT, and the peaks in the range of 160.4 to 161.4 eV were considered to be the peaks derived from the S atoms other than the above.
[0153] In addition, in the central part in the thickness direction of the surface layer 14 composed of silver containing carbon and sulfur, in the silver-plated material obtained in Example 25, the S atom concentration of S atoms derived from the mercapto group of SMBT was 0.4at%, the S atom concentration of S atoms derived from the five-membered ring of SMBT was 0.6at%, and the atomic concentration of S atoms derived from the mercapto group of SMBT and the S atoms derived from the five-membered ring of SMBT was 1.0at% in total, and the S atom concentration other than these was 0.8at%. In the silver-plated material obtained in Example 26, the S atom concentration of S atoms derived from the mercapto group of SMBT was 0.3at%, The S atomic concentration of S atoms derived from the five-membered ring of SMBT is 0.2at%, the atomic concentration of S atoms derived from the thiol group of SMBT and S atoms derived from the five-membered ring of SMBT is 0.5at% in total, and the S atomic concentration of other than these is 0.5at%; in the surface layer 14 composed of silver containing carbon and sulfur of the silver-plated material obtained in Example 25 and Example 26, it was confirmed that the atomic concentration of S atoms derived from the thiol group of SMBT and S atoms derived from the five-membered ring of SMBT is more than 0.3at% in total, and S derived from SMBT is present in the surface layer 14 composed of silver containing carbon and sulfur.
[0154] On the other hand, in the central portion in the thickness direction of the base silver-plated film 12, in the silver-plated material obtained in Example 25, the S atom concentration of the S atoms derived from the mercapto groups of SMBT was 0.0 at%, the S atom concentration of the S atoms derived from the five-membered ring of SMBT was 0.1 at%, the atomic concentration of the S atoms derived from the mercapto groups of SMBT and the S atoms derived from the five-membered ring of SMBT was 0.1 at% in total, and the S atom concentration of the rest was 0.1 at%. In the silver-plated material obtained in Example 26, the S atom concentration of the S atoms derived from the mercapto groups of SMBT was 0. .0at%, the S atomic concentration of S atoms derived from the five-membered ring of SMBT is 0.1at%, the atomic concentration of S atoms derived from the thiol group of SMBT and the S atoms derived from the five-membered ring of SMBT is 0.1at% in total, and the S atom concentration other than these is 0.1at%; in the base silver-plated film 12 of the silver-plated material obtained in Examples 25 and 26, it was confirmed that the atomic concentration of S atoms derived from the thiol group of SMBT and the S atoms derived from the five-membered ring of SMBT is less than 0.3at% in total, which is a value close to the error level of the analysis limit.
[0155] In addition, the silver-plated materials obtained in Examples 3, 29 and 30 were bent at 90° to a bending radius of R = 3 mm, and cracks in the silver-plated film were observed using an optical microscope. As a result, the silver-plated material of Example 3 had cracks of a relatively small degree that did not cause any practical problems, and the silver-plated materials of Examples 29 and 30 had fewer cracks. From these examples, it can be seen that when the silver-plated material is subjected to severe bending processing, the thickness of the underlying nickel film is preferably about 0.05 to 1.5 μm. Explanation of symbols
[0156] 10 base coating film 12 base silver-plated film 14 Surface layer composed of silver (silver-plated film).
Claims
1. A method for producing a silver-plated material, comprising forming a base silver-plated film on a raw material via a base plated film, and then electroplating the raw material in a silver-plating solution composed of an aqueous solution containing potassium silver cyanide or silver cyanide, potassium cyanide or sodium cyanide, and benzothiazoles or derivatives thereof, thereby forming a surface layer composed of silver containing carbon and sulfur on the base silver-plated film.
2. The method for producing a silver-plated material according to claim 1, wherein: The thickness of the base silver-plated film is 0.06-15 μm.
3. The method for producing a silver-plated material according to claim 1, wherein: The benzothiazole is mercaptobenzothiazole.
4. The method for producing a silver-plated material according to claim 1, wherein: The derivatives of the benzothiazoles are alkali metal salts of the benzothiazoles.
5. The method for manufacturing a silver-plated material according to claim 4, characterized in that: The alkali metal salt is a sodium salt.
6. The method for manufacturing a silver-plated material according to claim 1, wherein: The base plating film is composed of copper, nickel or an alloy thereof.
7. The method for manufacturing a silver-plated material according to claim 1, wherein: The raw material consists of copper or a copper alloy.
8. The silver-plated material according to claim 1, characterized in that: A base silver-plated film is formed on the raw material via a base plated film, and a surface layer composed of silver containing carbon and sulfur is formed on the base silver-plated film. The Ag atomic concentration in the base silver-plated film is higher than 95at%, the S atomic concentration is lower than 0.6at%, and the ratio of the C atomic concentration to the Ag atomic concentration is lower than 3%. The Ag atomic concentration in the surface layer composed of silver containing carbon and sulfur is lower than 95at%, the S atomic concentration is higher than 0.6at%, and the ratio of the C atomic concentration to the Ag atomic concentration is higher than 3%.
9. The silver-plated material according to claim 8, characterized in that The thickness of the base silver-plated film is 0.06-15 μm.
10. The silver-plated material according to claim 8, characterized in that The average crystallite size of silver in the silver-plated material is less than 100 nm.
11. The silver-plated material according to claim 8, characterized in that The Vickers hardness HV of the surface of the silver-plated material is 70-160.
12. The silver-plated material according to claim 8, characterized in that The base plating film is composed of copper, nickel or an alloy thereof.
13. The silver-plated material according to claim 8, characterized in that The raw material consists of copper or a copper alloy.
14. The silver-plated material according to claim 8, characterized in that The total concentration of S atoms of mercapto groups and five-membered S elements derived from mercaptobenzothiazole in the surface layer composed of silver containing carbon and sulfur is greater than 0.3 at %, and the total concentration of S atoms of mercapto groups and five-membered S elements derived from mercaptobenzothiazole in the base silver-plated film is less than 0.3 at %.
15. The silver-plated material according to claim 8, characterized in that For the surface layer composed of silver containing carbon and sulfur, when measured by X-ray photoelectron spectroscopy, the total of the S atomic concentration obtained from the spectrum with a peak in the range of 161.6 to 162.9 eV and the S atomic concentration obtained from the spectrum with a peak in the range of 163.2 to 164.5 eV is greater than 0.3 at %; for the base silver-plated film, when measured by X-ray photoelectron spectroscopy, the total of the S atomic concentration obtained from the spectrum with a peak in the range of 161.6 to 162.9 eV and the S atomic concentration obtained from the spectrum with a peak in the range of 163.2 to 164.5 eV is less than 0.3 at %.
Citation Information
Patent Citations
Terminal connector for connecting microwave converter to waveguide
JP1988030004A
Copper or copper alloy member having silver alloy layer formed as outermost surface layer, and manufacturing method therefor
JP2009079250A